2009
DOI: 10.1002/mrm.22146
|View full text |Cite
|
Sign up to set email alerts
|

In vivo proton MRS to quantify anesthetic effects of pentobarbital on cerebral metabolism and brain activity in rat

Abstract: To quantitatively investigate the effects of pentobarbital anesthesia on brain activity, brain metabolite concentrations and cerebral metabolic rate of glucose, in vivo proton MR spectra, and electroencephalography were measured in the rat brain with various doses of pentobarbital. The results show that (1) the resonances attributed to propylene glycol, a solvent in pentobarbital injection solution, can be robustly detected and quantified in the brain; (2) the concentration of most brain metabolites remained c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
25
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 43 publications
6
25
1
Order By: Relevance
“…First, the values of CMR glc , T max , and K T determined by the dynamic post glucose infusion measurement and the standard dynamic MichaelisMenten model were 0.44 ± 0.17 mmol/g per minute, 1.35 ± 0.47 mmol/g per minute, and 13.4 ± 6.8 mmol/ L, respectively, and are in good agreement with the values reported in the literature (Brender et al, 1975;Chen et al, 1993;Du et al, 2009;Lei and Gruetter, 2006;Mason et al, 1992;Ori et al, 1986;Pardridge, 1984). Specifically, the K T value has been reported to be 13.9 ± 2.7 mmol/L from an in-vivo MRS study (Mason et al, 1992), and 11.0 mmol/L as well as T max = 1.4 to 1.6 mmol/g per minute measured by the radioactive tracer method (Brender et al, 1975;Pardridge, 1984), respectively.…”
Section: Simultaneous Measurement Of T Max K T and Cmr Glc In Ratsupporting
confidence: 87%
See 1 more Smart Citation
“…First, the values of CMR glc , T max , and K T determined by the dynamic post glucose infusion measurement and the standard dynamic MichaelisMenten model were 0.44 ± 0.17 mmol/g per minute, 1.35 ± 0.47 mmol/g per minute, and 13.4 ± 6.8 mmol/ L, respectively, and are in good agreement with the values reported in the literature (Brender et al, 1975;Chen et al, 1993;Du et al, 2009;Lei and Gruetter, 2006;Mason et al, 1992;Ori et al, 1986;Pardridge, 1984). Specifically, the K T value has been reported to be 13.9 ± 2.7 mmol/L from an in-vivo MRS study (Mason et al, 1992), and 11.0 mmol/L as well as T max = 1.4 to 1.6 mmol/g per minute measured by the radioactive tracer method (Brender et al, 1975;Pardridge, 1984), respectively.…”
Section: Simultaneous Measurement Of T Max K T and Cmr Glc In Ratsupporting
confidence: 87%
“…This finding seemingly contradicts other studies that show a decreased brain glucose concentration accompanied by an increased CMR glc due to the elevated neuronal activity by visual stimulations (Chen et al, 1993;Mangia et al, 2007;Merboldt et al, 1992). However, this apparent discrepancy can be explained by the glucose transport regulation and plasma glucose concentration alteration, which was substantially decreased under the isoelectric condition (Du et al, 2009). A significant reduction in plasma glucose level could lead to a large decrease in brain glucose concentration, since the brain glucose concentration is tightly coupled to the plasma glucose concentration and is regulated by the glucose transport across BBB.…”
Section: Introductioncontrasting
confidence: 77%
“…Previous work indicated that in vivo 31 P MT provides a non-invasive approach for directly studying bioenergetics/mitochondrial function associated with brain activity changes (1214, 24, 26). The major obstacle to this approach is the low signal-to-noise ratio (SNR) especially for ATP syn reaction measurements because of the intrinsically low nuclear gyromagnetic ratio of 31 P and the low concentration of Pi (~1mM).…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, extrapolation of the metabolic parameters to humans is guarded. Further, we imaged mice under anesthesia, which is known to alter brain metabolic profiles [31,32]. The quantitative parameters in this work are thus relative and not absolute.…”
Section: Discussionmentioning
confidence: 99%